The Effects of Parathyroid Hormone Applied at Different Regimes on the Trochanteric Region of the Femur in Ovariectomized Rat Model of Osteoporosis - M. Tezval; A. Banhardt; S. Sehmisch; L. Kolios; U. Schmelz; K. M. Stuermer; E. K. Stuermer (Journal of Osteoporosis)
This study aims to investigate the effects of two application frequencies of parathyroid hormone on the trochanteric region of rat femur. Forty-three-month-old female Sprague-Dawley rats were divided into 4 groups (n=10/group). Three groups were ovariectomized, and 8 weeks later they were administered the following treatments (5 weeks): soy-free diet (OVX), subcutaneously injected PTH (0.040 mg/kg) 5 days a week (PTH 5x/w), subcutaneously injected PTH (0.040 mg/kg) every 2 days (PTH e2d), and a sham group. The values of the biomechanical and histomorphometric parameters showed higher results in 5x/w animals in comparison to the OVX and PTH 2ed groups. The ratio between bone diameter/marrow diameter (B.Dm/Ma.Dm) in subtrochanteric cross sections did not show any significant differences between PTH 5x/w and PTH e2d. The increased bone formation rate was observed under PTH treatment in both groups mainly at the endosteal side. The endosteum seems here to be one of the targets of PTH with an accelerate bone formation and a pronounced filling-in of intracortical cavities with higher intensity for the PTH 5x/w in comparison to PTH e2d rats.